X‐ray studies of three 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine cocrystals: an unexpected molecular conformation stabilized by hydrogen bonds. Issue 2 (18th January 2023) - Wzgarda-Raj, Kinga; Dominikowska, Justyna; Wojtulewski, Sławomir; Rybarczyk-Pirek, Agnieszka J.
Abstract : The results of the X‐ray structure analysis of three novel 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine cocrystals are presented. Quantum chemistry methods are used to describe the conformational diversity of 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine. An analysis is made of the intermolecular interactions stabilizing the crystal structures and the observed conformations. Abstract : The results of the X‐ray structure analysis of three novel 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine cocrystals are presented. These are 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine–2, 4, 6‐tribromophenol (1/2), C12 H8 N6 ·2C6 H3 Br3 O, 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine–isonicotinic acid N ‐oxide (1/2), C12 H8 N6 ·2C6 H5 NO3, and 3, 6‐bis(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine–4‐nitrobenzenesulfonamide (1/1), C12 H8 N6 ·C6 H6 N2 O4 S. Special attention is paid to a conformational analysis of the title tetrazine molecule in known crystal structures. Quantum chemistry methods are used to compare the energetic parameters of the investigated conformations. A structural analysis of the hydrogen and halogen bonds with acceptor aromatic tetrazine and pyrazine rings is conducted in order to elucidate factors responsible for conformational stability.